The Role of Development Towards a Sustainable Economy - Prilian, Pinindita Trias (Universitas PGRI Madiun, 2025)
The purpose of this study is to determine how the role of law in driving the dynamics of national economic development is reviewed from the principle of people's economy through several discussions on the urgency of national economic legal development, the second is how the role of law in driving the dynamics of national economic development is reviewed from the principle of sustainable economy, as well as national economic development strategies with the principle of sustainable economy. This type of research is Library Research, namely research through library or literature studies. The data source in this study is primary data, namely books that directly discuss the role of development towards a sustainable economy. The data analysis technique used to obtain conclusions is deductive, namely the method of drawing conclusions from general to specific. The results of this study The concept or role of law of the Indonesian national economy must adhere to the principle of family, people's sovereignty, Pancasila morals, and show partiality to the people's economy. This concept of sustainable development can only be guaranteed by law and this law that guarantees it must also continue to carry out development in order to be able to jointly carry out national development to prosper its people. Sustainable development strategies, which include development that ensures equity and social justice, development that respects diversity, development that uses an integrative approach, and development that requires a long-term perspective